Exploring Contemporary Tafsir: Uncovering Pluralistic Values in Nusantara Tafsir - Affandi, Abdullah (SAMAWAT: JOURNAL OF HADITH AND QURANIC STUDIES, 2025)
This article explores the significant role of Nusantara Tafsir in promoting pluralistic values and fostering interfaith dialogue within Indonesia's diverse cultural landscape. Through the analysis of key works by prominent scholars such as Hamka and Quraish Shihab, the study highlights how these interpretations contextualize Quranic teachings to address contemporary social issues while emphasizing values such as tolerance, respect, and social justice. The case studies presented illustrate the unique characteristics of Nusantara Tafsir, including its integration of local wisdom and cultural practices, which enhance the relevance of Islamic teachings in the Indonesian context. Furthermore, the article discusses the contributions of Nusantara Tafsir to interfaith dialogue, emphasizing its role in promoting understanding and cooperation among different religious communities. By advocating for shared values and collaborative efforts, Nusantara Tafsir serves as a vital resource for building harmonious relationships in a pluralistic society. The findings underscore the importance of educational initiatives, interfaith dialogue programs, and grassroots movements in furthering the impact of Nusantara Tafsir on social harmony and understanding. This research contributes to the ongoing discourse on the relevance of Islamic teachings in addressing contemporary challenges and fostering a more inclusive society in Indonesia